Comparison of Health-Related Quality of Life Changes in Prostate Cancer Patients Undergoing Laparoscopic versus Robotic-Assisted Laparoscopic Radical Prostatectomy: A Systematic review - Yazici, Sertac; Tonyali, Senol (Urology Journal, 2024)
Purpose: To compare the effects of RALP and LRP on health-related QoL following radical prostatectomy, focusing on studies performed via validated QoL questionnaires measuring particularly general health-related QoL. Material and Methods: A systematic search was conducted using Web of Science, PubMed (MEDLINE) on 15 January 2023 with the following search terms solely or in combination: "robotic radical prostatectomy", "laparoscopic radical prostatectomy," and "quality of life". After retrieving the titles and abstracts of selected articles, the full texts of related articles were screened. Results: After full-text evaluation, among 185 articles, 23 articles were found eligible for inclusion. Hoze et al. reported that the global health status at the 12th month of the surgery was almost the same in both groups according to EORTC- QLQ-C30 scores (76.3 in the RALRP group vs. 76.1 in the LRP group). Wang et al. reported a 75 point of EORTC-QOL-C30 global health status ten years after LRP. Wyler et al. found that the 1-3 month EORTC-QLQ-C30 global health score was significantly worser than the baseline score, 65.3±18.3 vs. 77.2±18.2; however, it returned to baseline in 13-24 months (77.7±16.8) even proceed baseline score in experienced hands at 49-58 months follow up, 78.2±17.8 vs. 85.3±15.5. The frequently used patient-reported quality of life questionnaire following RALRP was EORTC-QLQ. Conclusion: Both robotic-assisted and laparoscopic radical prostatectomy are valid treatment options to achieve a good quality of life following surgery. The intermediate and long-term results in regard to QoL are comparable between the two procedures. RALRP might be superior to LRP in terms of immediate health-related quality of life, which might contribute to early recovery of urinary function.